Grain growth study of perovskite thin films prepared by flash evaporation and its effect on solar cell performance. Issue 54 (18th May 2016) - Xu, Haitao; Wu, Yanglin; Xu, Fuzong; Zhu, Jiabin; Ni, Chaowei; Wang, Wenzhen; Hong, Feng; Xu, Run; Xu, Fei; Huang, Jian; Wang, Linjun
Abstract : Flash-evaporated perovskite films with large grain sizes lead to high efficiency solar cell devices. Abstract : Flash evaporation is a vacuum-based evaporation method that is particularly suitable to prepare perovskite films for solar cell devices. Growth pressure has been found to be a critical parameter for perovskite film growth. The transport-determined growth mechanism is discussed in detail. The dense MAPbI3 films can be achieved only under a low growth pressure of 5 × 10 −3 Pa, while a rough surface covered by step-like grains and voids is found for MAPbI3 films grown under a high Ar pressure of 10 Pa. In addition, we found that the presence of PbI2 phase in the perovskite films could suppress the growth of the grain size; by using precursors with a high MAI/PbI2 ratio, evaporated MAPbI3 films with grain sizes larger than 500 nm can be achieved. The average power conversion efficiency of the perovskite solar cells increased from 1.82% to 10.01% with increasing grain size, indicating the universal importance of controlling the perovskite grain size for the performance improvement of solar cells based on both solution and evaporated perovskite films.